Predicting the nature of supernova progenitors. (28th October 2017) - Groh, Jose H.
Abstract : Stars more massive than about 8 solar masses end their lives as a supernova (SN), an event of fundamental importance Universe-wide. The physical properties of massive stars before the SN event are very uncertain, both from theoretical and observational perspectives. In this article, I briefly review recent efforts to predict the nature of stars before death, in particular, by performing coupled stellar evolution and atmosphere modelling of single stars in the pre-SN stage. These models are able to predict the high-resolution spectrum and broadband photometry, which can then be directly compared with the observations of core-collapse SN progenitors. The predictions for the spectral types of massive stars before death can be surprising. Depending on the initial mass and rotation, single star models indicate that massive stars die as red supergiants, yellow hypergiants, luminous blue variables and Wolf–Rayet stars of the WN and WO subtypes. I finish by assessing the detectability of SN Ibc progenitors. This article is part of the themed issue 'Bridging the gap: from massive stars to supernovae'.